Prediction model of financial distress reporting of multifinance companies in 2017-2021 in Indonesia - Ismail, Ilham; Ispriyadi, Heri; Simanullang, Saiful; Rukmana, Heru Satria (Technium Social Sciences Journal, 2023)
The urgency of this study is because the phenomenon of the Covid-19 pandemic is the cause of many multifinance companies to have an impact on decreasing the quality of financial performance so that it has the potential for financial distress, while the purpose of this study is to determine and analyze the effect of liquidity, solvency and profitability on one of the 7 most accurate bankruptcy prediction models. The sample method used is a purposive sampling technique with criteria, namely (1) companies engaged in financing (multi finance), (2) Meeting data needs, from 100 samples get 34 companies, analyzing data calculations by calculating financial performance and 7 bankruptcy prediction models, 1 bankruptcy prediction model is chosen that is the most accurate with the lowest number of companies predicting risk to see the effect using data regression panel because the financial statements are reviewed in a time series of 5 years period, the research method used with the number of research samples is 34 companies from 100 populations, with a comparative analysis method of 7 bankruptcy models, influence tests with classical assumption tests and regression panel data because the financial statements are reviewed in a 5-year time series period, the results obtained are that the analysis of financial performance is based on predetermined ratios Describes an increase every year in several companies, and indicates that 34 companies have very good financial positions. bankruptcy analysis from 7 methods, there are 3 companies 3 times in a row to get distress conclusions, namely Bosowa Multifinance, Anugerah Buana Central Multi Finance and Batavia Prosperindo Finance Tbk. In addition, the relevant bankruptcy prediction in this study uses a Z Score where the results are assessed because a positive Z Score value indicates a lower level of bankruptcy risk, The results of the influence test result that the variables of liquidity, solvency and profitability affect the Bankruptcy Prediction, the managerial implications obtained even though the company is considered good but still must be controlled and evaluated financial management every period.